2019
DOI: 10.3390/en12224338
|View full text |Cite
|
Sign up to set email alerts
|

State-of-Health Estimation of Li-ion Batteries in Electric Vehicle Using IndRNN under Variable Load Condition

Abstract: In electric vehicles (EVs), battery management systems (BMS) carry out various functions for effective utilization of stored energy in lithium-ion batteries (LIBs). Among numerous functions performed by the BMS, estimating the state of health (SOH) is an essential and challenging task to be accomplished at regular intervals. Accurate estimation of SOH ensures battery reliability by computing remaining lifetime and forecasting its failure conditions to avoid battery risk. Accurate estimation of SOH is challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Future research is directed towards the development of protecting the wireless charging system against attacks such as Jamming attacks [165]- [168], Spoofing attacks [166], [196], Safety attacks [196], [197], Interference attacks [196], Software attacks [166], [196], [198] and Monitoring attack [196]. Furthermore, research is directed towards the development of energy-saving systems [199], handling large UAV protocol data [200], avoiding charging conflicts [169]- [174], design of novel coil structures [149], [151], [152], drone to drone (V2V) charging [175], Supercapacitor based fast charging [176], dynamic charging of UAV during long flight hours [177], [178], Efficient battery management of UAV for optimized performance [179]- [181], development of coordination algorithms [182], [183], using UAVs for 5G/6G communication [184], [185], accurate drone landing algorithms using image processing techniques [186]- [188] and studying effects of EM waves on the human body [189].…”
Section: Future Trends and Research Directionsmentioning
confidence: 99%
“…Future research is directed towards the development of protecting the wireless charging system against attacks such as Jamming attacks [165]- [168], Spoofing attacks [166], [196], Safety attacks [196], [197], Interference attacks [196], Software attacks [166], [196], [198] and Monitoring attack [196]. Furthermore, research is directed towards the development of energy-saving systems [199], handling large UAV protocol data [200], avoiding charging conflicts [169]- [174], design of novel coil structures [149], [151], [152], drone to drone (V2V) charging [175], Supercapacitor based fast charging [176], dynamic charging of UAV during long flight hours [177], [178], Efficient battery management of UAV for optimized performance [179]- [181], development of coordination algorithms [182], [183], using UAVs for 5G/6G communication [184], [185], accurate drone landing algorithms using image processing techniques [186]- [188] and studying effects of EM waves on the human body [189].…”
Section: Future Trends and Research Directionsmentioning
confidence: 99%
“…ML techniques such as Fuzzy Logic (FL), Support Vector Machine (SVM) and Artificial Neural Networks (ANN) have extensively been applied for the estimation of the health of batteries, and a brief review can be found in [3]. In most cases, SoH is estimated by determining battery capacity and internal resistance, parameters strictly related to SoH, from input variables behaviour analysis (current, temperature, voltage, etc.)…”
Section: Algorithms For State Of Health (Soh) and Remaining Useful Life (Rul) Evaluation: A Brief Reviewmentioning
confidence: 99%
“…An application of Fuzzy logic with a potential use in portable devices is reported in [19], where Electrochemical Impedance Spectroscopy (EIS) technique was used for the dataset creation. However, improper hypotheses in the Fuzzy rules [3] and reduced set of observations can lead to substantial errors. The Support Vector Machine is a regression algorithm which converts nonlinearities in a lower dimension space to a linear model developed in a higher-dimensional one [20].…”
Section: Algorithms For State Of Health (Soh) and Remaining Useful Life (Rul) Evaluation: A Brief Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The lithium-ion (Li-ion) battery is widely used in electric vehicles because of its exceptional high cell voltage, high energy density, electromotive force, high output voltage, long lifetime, high charging efficiency, low self-discharge, low voltage drop, easy maintenance, and recycle [2], [3], [4]. These advantages have contributed to wider applications of lithium-ion batteries in more areas such as vehicles, household equipment, communications, aerospace, and other fields [5].…”
Section: Introductionmentioning
confidence: 99%